Health-related quality of life and associated factors among patients with stroke at tertiary level hospitals in Ethiopia. - Ashenafi Zemed; Kalkidan Nigussie Chala; Getachew Azeze Eriku; Andualem Yalew Aschalew (PLoS ONE)
Introduction Evidence on a patient-centered assessment of outcome among patients with stroke is limited in Ethiopia. Therefore, this study aimed to assess the level of health-related quality of life (HRQOL) and associated factors in Ethiopia's tertiary level hospitals. Methods A cross-sectional study was conducted at three tertiary level hospitals (Felege Hiwot comprehensive specialized hospital, University of Gondar comprehensive specialized hospital, and Dessie referral hospital) from April 1 to May 31, 2019. A total of 180 patients with stroke were included, and a consecutive sampling method was employed to recruit the participants. RAND 36-Item Health Survey was used to measure the HRQOL. A generalized linear model with a gamma distribution and log-link function was used to investigate potential predictors, and variables with a P value of <0.05 were considered statistically significant. Results Out of the participants, 50.56% were female. The average age and average duration of illness were 59.04 (12.71) and 1.5 (1.46) years, correspondingly. The physical health domain score was higher than the mental health domain score. Education (P = 0.041), social support (P = 0.050), disability (P <0.001), co-morbidity (P = 0.011), depression (P = 0.015) and income (<1000 ETB P = 0.002; 1000-4000 ETB P = 0.009) were associated with physical health domain. Whereas, ischemic stroke (P = 0.014), education (P = 0.020), disability (P <0.001), and depression (P <0.001) were associated with the mental health domain. Conclusion The HRQOL of the patients was low. Social support and lower disability status were associated with higher HRQOL, whereas disability and depression were associated with higher HRQOL. Therefore, attention should be given to strengthening social support; health professionals should focus on reducing disability/physical dependency and depression, as these are vital factors for improving HRQOL.